Strengthening of the mechanical and tribological properties of composite oxide film formed on aluminum alloy with the addition of graphite - Mohamad, Syazwani; Shahira Liza; Yaakob, Yazid (Elsevier, 2020)
Composite oxide films containing graphite were fabricated using the anodizing technique on AA2017- T4 aluminum alloy in diluted sulfuric acid (20 wt%). This study aims to evaluate the effect of graphite on the film growth and investigate its impact on the self-lubricating ability and durability of the composite films. The growth mechanism was determined by manipulating the anodizing time while the mechanical and tribological properties of the films were studied with different graphite content. The surface morphology, topography, and chemical compositions were examined with scanning electron microscopy (SEM), 3D optical profiler, and energy- dispersive spectroscopy (EDS), respectively. The microhardness was characterized at the surface and cross-section of the films by Vickers microhardness tester. The structure of the oxide films and graphite were studied by X-ray diffractometer (XRD) and Raman spectroscopy. The tribological characterization was investigated by using a ball-on-disk sliding test in dry condition. The growth of the film was initiated by the formation of the non-porous barrier layer at 5–10 min. The pores started to grow at 20 min and caused the break of the barrier layer. For this process, the complete development of porous composite oxide film can be achieved at 60 min with the pore dimension (width: 23.74 ± 8.91 μm; depth: 27.9 ± 9.09 μm). The thickness of 1 g/L oxide film at 60 min was about 32.45 ± 4.92 μm, approximately. The incorporation of graphite reduces the surface porosity of oxide films and improves the mechanical and tribological properties significantly. The service life of the composite oxide film is affected by the hardness and graphite-self-lubricated layer.